Desempenho ocupacional de crianças com comprometimento na expressão escrita - Campos, Sara Domiciano Franco de (2023)
The work of occupational therapists focuses on the performance and engagement of people in their occupations. In this sense, school constitutes a typical occupation in childhood. Studies report that about 30% to 40% of children who have learning difficulties also have difficulties in writing and deficits that appear within the school. The general objective of this study was to identify children with impairment in writing expression, possible problems for occupational performance at school and correlations with motor skills, memory and attention. This is a correlational descriptive study with quantitative analysis, and each of the instruments used has the respective arithmetic procedures for analyzing the responses obtained. The research was approved by the Ethics and Research Committee of the Federal University of São Carlos, and acceptance and signature of the Term of Free and Informed Consent and the Term of Free and Clarified Assent. The research sample consisted of 19 children aged between 8 and 10 years, regularly enrolled in a public school in the interior of the State of São Paulo, indicated by the teachers for presenting impairment in written expression, with the exclusion criterion being the child have a diagnosis of a disability and/or developmental disorder. For data collection, the School Performance Test (TDE-II), Movement Assessment Battery for Children (M-ABC II), Cancellation Attention Test (TAC), Block Span Task - CORSI (TSB-C), Digit Span Task (TSD) and a questionnaire on occupational performance, created by the researcher. The results showed that children have very severe difficulty (n=78.95%) in writing and severe difficulty (n=21.05%) measured by TDE-II. It is observed that of these children with impaired written expression, 68.42% had a low score for age in relation to alternating attention (measured by TAC) and 31.58% had a low score for age in relation to complex selective attention ( measured by TAC). Of this sample, 42.11% had low scores for age in relation to short-term memory and visuospatial working memory (measured by TSB-C OI) and 26.32% had low scores for age in auditory memory short-term (measured by the TSD-OI). With regard to the general motor performance measured by the M-ABC 2, 26.32% of the children classified themselves as having motor difficulties, and specifically 15.79% classified themselves as having difficulty with manual dexterity, difficulty aiming and picking up, and difficulty of balance. Regarding occupational performance, there was impairment in occupational performance at school, with 29.55% of the children considered unable to perform, 19.70% only performing with parental assistance and 34.09% performing alone, however, with great difficulty. The research identified that the children in this study with impairment in writing expression, presented difficulties in their occupational performance at school and impairment in memory and attention components, corroborated with the literature, but did not present impairment in the motor component, being this hypothesis of study refuted despite the literature indicating a relationship between them.